Cellular pharmacokinetic/pharmacodynamic relationship of platinum cytostatics in head and neck squamous cell carcinoma evaluated by liquid chromatography coupled to tandem mass spectrometry - Theile, Dirk; Detering, Jan-Christoph; Herold-Mende, Christel; Dyckhoff, Gerhard; Haefeli, Walter E.; Weiß, Johanna; Burhenne, Jürgen (The journal of pharmacology and experimental therapeutics, 2012)
Cisplatin (diaminodichloroplatinum) is the favored platinum (Pt) drug for the treatment of head and neck squamous cell carcinoma (HNSCC). However, Pt drug alternatives such as carboplatin (diaminoplatinum-cyclobutan-1,1-dicarboxylate) or oxaliplatin [oxalato[(1R, 2R)-cyclohexanediamino] platinum] have not been comprehensively investigated in HNSCC. Moreover, little data reveal the decisive efficacy determinant and whether Pt drug efficacy is truly concentration-dependent. Using five human HNSCC cell lines, we determined the concentrations of cisplatin, carboplatin, and oxaliplatin leading to 50% inhibition of cell proliferation (IC50). Concurrently we quantified cellular drug uptake by liquid chromatography coupled to tandem mass spectrometry and evaluated mRNA expression of drug transporters involved in Pt drug uptake by quantitative real-time polymerase chain reaction. Mean IC50 among the five cell lines was 6.2 +/- 1.9 mu M for cisplatin and 11.6 +/- 4.2 mu M for oxaliplatin, whereas carboplatin showed significantly lower proliferation inhibition (IC50 107.5 +/- 21.2 mu M). In agreement with this finding carboplatin poorly accumulated in HNSCC cells, compared with cisplatin and oxaliplatin. HNSCC cell lines expressed Pt drug transporters. Taken together, the results demonstrate: 1) carboplatin was less effective and was poorly taken up; 2) a high individuality among cell lines was found concerning the accumulation of cisplatin and oxaliplatin despite similar in vitro efficacy; and 3) distinct expression of SLC22A2 and ABCC2 accompanies strong uptake and cytotoxicity of Pt drugs. In conclusion, we demonstrate that in vitro efficacy of cisplatin and oxaliplatin in HNSCC is concentration-independent because they exhibited different uptake characteristics but similar efficacies, suggesting oxaliplatin as a promising alternative against HNSCC that needs further evaluation in clinical trials.
Gesehen am 09.04.2018